2002
DOI: 10.1063/1.1448406
|View full text |Cite|
|
Sign up to set email alerts
|

Patterned ferro-, pyro- and piezoelectricity in poly(vinylidene fluoride) by means of a laser-induced irreversible β→α phase transformation

Abstract: Materials with patterned pyro- or piezoelectricity are useful for a range of applications such as sensor arrays with reduced cross talk between individual elements, piezoelectric gratings for direction-sensitive acoustic-wave detection/emission, or motion-sensitive pyroelectric sensors. Here, the successful patterning of pyro- and piezoelectric poly(vinylidene fluoride) (PVDF) films, by controlled scanning of a focused laser beam across their top electrodes, is reported. The resulting patterns are based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…13,14 PSM works with crystals [13][14][15][16][17][18][19] and with thin films. [20][21][22][23] PSM has also been used to image domains 14,24 thermally written polarization patterns, [25][26][27][28] and to follow polarization and domain dynamics. [29][30][31][32] Moreover, 3D polarization information can be obtained from crystals and thick films by combining 2D laser scanning with depth profiles obtained using either pulse time-of-flight methods, 33 or Laser Intensity Modulation Method (LIMM), [34][35][36][37][38] or both.…”
mentioning
confidence: 99%
“…13,14 PSM works with crystals [13][14][15][16][17][18][19] and with thin films. [20][21][22][23] PSM has also been used to image domains 14,24 thermally written polarization patterns, [25][26][27][28] and to follow polarization and domain dynamics. [29][30][31][32] Moreover, 3D polarization information can be obtained from crystals and thick films by combining 2D laser scanning with depth profiles obtained using either pulse time-of-flight methods, 33 or Laser Intensity Modulation Method (LIMM), [34][35][36][37][38] or both.…”
mentioning
confidence: 99%
“…A less damaging method is to locally heat the film through a phase change, such as the melting point or ferroelec tric Curie temperature [4]. Polarization patterning by la ser-induced phase change has been demonstrated with ferroelectric polymer thin films, but mainly through melting, photochemical alteration, or other irrevers ible alterations [5,6]. Reversible patterning, however, can be accomplished in ferroelectric films due to the re versibility of the ferroelectric-paraelectric phase transi tion in these materials [7].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Its piezo/pyroelectric properties have enabled the fabrication of film-based tactile sensors,infrared detectors,e nergy-harvesting devices,a nd non-volatile memories.T orealize these applications,itiscritical to pattern the ferroelectric phase (either b or g)rather than the paraelectric a phase.T hus far,s uch patterning has mainly been achieved by irradiation etching [9] and imprinting lithography. [12] This method successfully generated depolarized stripes with aw idth of 80-90 mmi naP VDF film, but the efficiency is expected to be relatively low owing to the high reflectance of the metal electrode and the one-direction heat transfer from the electrode to the film.Herein, we demonstrate the use of plasmonic nanostructures to harvest photon energy as an effective means to induce ferroelectric-paraelectric phase transitions in af erroelectric polymer film. 170 8 8C).…”
mentioning
confidence: 99%
“…[10] The former method may deteriorate the ferroelectric properties whereas it is not easy to obtain af reestanding and smooth polymer film using imprinting lithography without requiring multiple steps.P VDF generally exhibits ap hase transition from the ferroelectric to the paraelectric phase when heated to temperatures near its melting point or the ferroelectric Curie temperature (ca. [12] This method successfully generated depolarized stripes with aw idth of 80-90 mmi naP VDF film, but the efficiency is expected to be relatively low owing to the high reflectance of the metal electrode and the one-direction heat transfer from the electrode to the film. [11] As an alternative approach, Wegener et al reported the patterning of aP VDF film by scanning af ocused laser beam across the top aluminum electrode.…”
mentioning
confidence: 99%
See 1 more Smart Citation